Activity-dependent refinement of axonal projections forms one-to-one connection pattern in the developing chick ciliary ganglion - Egawa, Ryo; Yawo, Hiromu; Kuba, Hiroshi (Frontiers in Cellular Neuroscience, 2025)
Although it is well established that initially overproduced synaptic connections are extensively remodeled through activity-dependent competition for postsynaptic innervation, the mechanisms determining the final number of postsynaptic targets per axon remain unclear. Here, we investigated the morphology of individual axonal projections during development and the influence of neural activity in the chick ciliary ganglion (CG), a traditional model system for synapse maturation. By single-axon tracing combining Brainbow labeling and tissue clearing, we revealed that by embryonic day 14 (E14), hundreds of preganglionic axons each establish a one-to-one synaptic connection with single CG neurons via a calyx-type presynaptic terminal enveloping the soma of its postsynaptic target. This homogeneous connection pattern emerged through presynaptic terminal maturation from bouton-like to calyx-like morphology and concurrent axonal branch pruning starting around E10. The calyx maturation was retarded by the presynaptic expression of genetically encoded tools for silencing neuronal activity, enhanced tetanus neurotoxin light chain (eTeNT) or Kir2.1, demonstrating the activity-dependence of this morphological refinement. These findings suggest that some presynaptic mechanisms as well as synaptic competition would operate to restrict the number of postsynaptic targets innervated by each axon in the CG. Together with the easy accessibility to single-axon tracing, our results highlight the potential of the chick CG as a model for investigating the presynaptic factors underlying circuit remodeling.